2022
DOI: 10.1038/s41523-022-00499-7
|View full text |Cite
|
Sign up to set email alerts
|

Histology-based survival outcomes in hormone receptor-positive metastatic breast cancer treated with targeted therapies

Abstract: The addition of targeted therapies (TT) to endocrine therapy (ET) has improved the outcomes of patients with HR-positive, HER2-negative metastatic breast cancer (mBC). However, it is unknown whether patients with invasive lobular carcinoma (ILC) or mixed invasive ductal and lobular carcinoma (mixed) histologies experience the same magnitude of benefit from this therapy as those with invasive ductal carcinoma (IDC). We aim to determine whether patients with IDC, ILC, and mixed HR+/HER2− mBC derive similar benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Unfortunately, histological subtyping was missing for more than half of the patients in these pooled analyses, and as a result, the analyses for ILC were performed only on a small number of patients ( n = 269). Several retrospective studies came to a similar conclusion that the benefit of CDK4/6 inhibitors is similar for metastatic ILC in comparison to IBC-NST 43 , 44 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Unfortunately, histological subtyping was missing for more than half of the patients in these pooled analyses, and as a result, the analyses for ILC were performed only on a small number of patients ( n = 269). Several retrospective studies came to a similar conclusion that the benefit of CDK4/6 inhibitors is similar for metastatic ILC in comparison to IBC-NST 43 , 44 .…”
Section: Discussionmentioning
confidence: 84%
“…Limited data exist that there is no significant difference in the benefit of everolimus between patients with metastatic ILC vs. IBC-NST 43 . A retrospective study concluded that patients with ILC benefit more from the combination of exemestane with everolimus than the combination of palbociclib with fulvestrant when used in second line of metastatic treatment in patients with hormone-resistant disease 45 .…”
Section: Discussionmentioning
confidence: 99%
“…However, several of these studies were limited by a low number of patients included 7 , 8 , or by the fact that the prognostic role of HER2 status was evaluated in heterogeneous patient cohorts, i.e., in patients with different tumor biology and receiving different types of systemic therapies 6 , 9 . A recent, large study from the MD Anderson Cancer Center did not find an association between HER2 status and clinical outcomes in 919 HR + /HER2- aBC patients treated with first-line ET plus CDK4/6 inhibitors 15 . Discrepancies across studies could derive from differences in the population of patients included (e.g., different patient- and tumor-related characteristics), diverse assessment of HER2 status, different clinical management of patients (e.g., different types of backbone ET or CDK4/6i compound used, different subsequent lines of therapy, and in particular T-DXd), or the inclusion of patients with different intrinsic BC subtypes 16 .…”
mentioning
confidence: 92%
“…Due to their serious metastasis and secondary infection, cancers have been the leading cause of human death. The general treatments of cancer include surgery [1,2], chemotherapy [3,4], radiotherapy [5,6], and so on. With the rapid development of nanotechnology and materials science [7][8][9][10], nano-drug delivery systems [11][12][13][14] have been widely concerned in the cancers' diagnosis [15] and treatment [16].…”
Section: Introductionmentioning
confidence: 99%